Clinical Trials in Chronic Liver Disease - What Do They Achieve? - Jenny Heathcote (Canadian Journal of Gastroenterology)
The past 30 years have seen rapid growth in the number of clinical trials in liver disease; due mostly to effective drug discovery programs by the pharmaceutical industry. The advantages associated with therapeutic trials in chronic liver disease, or any other disease for that matter, go far beyond potential benefit to the individual patient, other beneficiaries include the treating physician, the sponsoring agency and their investors, the institution/university and the general public. But there is always a downside to any experiment. The disadvantages and advantages of clinical trials in liver disease are the topics for this discussion.